Regional self-reliance for livestock feed, meat, dairy and eggs in the Northeast USA. Issue 2 (4th April 2016) - Conrad, Zach; Tichenor, Nicole E.; Peters, Christian J.; Griffin, Timothy S.
Abstract: The production of livestock feed in the USA is geographically concentrated, which poses several risks. Extreme weather events and disease outbreaks have the potential to disrupt production in these areas, which could reduce the national output of meat, dairy and eggs. Additionally, geographically concentrated livestock and feed production systems have been observed to contribute excessive nutrient loads to surrounding soil and water bodies, thereby threatening environmental sustainability. Geographic relocation of production systems has been proposed as an adaptation strategy to increase system resilience and this could take the shape of more geographically dispersed livestock feed production. We estimate the degree to which the demand for meat, dairy and eggs in the Northeast region is met with current levels of regional feed and livestock production, a term that we refer to as regional self-reliance . We combine mean annual (2001–2010) data on Northeast regional land use; crop output; meat, dairy and egg output; and food consumption with a livestock feed requirements model. An annual mean of over 6.1 million ha of land in the Northeast was dedicated to livestock feed from 2001 to 2010, with nearly 80% located in just three states (Pennsylvania, New York and West Virginia). The region is a net importer of livestock feed (in terms of total digestible nutrients and crude protein), as well as meat, dairy and eggs (in terms of total human-edible energy and protein). This is the result of a confluence of long-term regional trends that include the movement of agricultural production out of the region with a concomitant increase in the regional population and an increase in the national demand for meat, dairy and eggs. Limited slaughter output in the region is a key limiting factor to increasing the region's self-reliance for livestock products.